2020
DOI: 10.1002/aur.2413
|View full text |Cite
|
Sign up to set email alerts
|

The Autism‐Related lncRNA MSNP1AS Regulates Moesin Protein to Influence the RhoA, Rac1, and PI3K/Akt Pathways and Regulate the Structure and Survival of Neurons

Abstract: Autism spectrum disorder (ASD) is a complex disease involving multiple genes and multiple sites, and it is closely related to environmental factors. It has been gradually revealed that long noncoding RNAs (lncRNAs) may regulate the pathogenesis of ASD at the epigenetic level. In neuronal cells, the lncRNA moesin pseudogene 1 antisense (MSNP1AS) forms a double-stranded RNA with moesin (MSN) to suppress moesin protein expression. MSNP1AS overexpression can activate the RhoA pathway and inhibit the Rac1 and PI3K/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Other studies showed that a certain single nucleotide polymorphism in the antisense transcript to a processed pseudogene of moesin ( MSNP1AS ) also could be present and upregulated in some ASD cases [ 197 ]. This lncRNA regulates the expression of moesin, which is an important factor in neurons regulating the immune response and architecture of the nucleus [ 3 , 65 , 198 , 199 ]. Upregulation of MSNP1AS leads to downregulation of moesin translation, negatively affecting neurite morphology and function [ 65 , 170 , 198 , 199 ].…”
Section: Lncrnas In Neurodevelopmental and Neuropsychiatric Disordersmentioning
confidence: 99%
“…Other studies showed that a certain single nucleotide polymorphism in the antisense transcript to a processed pseudogene of moesin ( MSNP1AS ) also could be present and upregulated in some ASD cases [ 197 ]. This lncRNA regulates the expression of moesin, which is an important factor in neurons regulating the immune response and architecture of the nucleus [ 3 , 65 , 198 , 199 ]. Upregulation of MSNP1AS leads to downregulation of moesin translation, negatively affecting neurite morphology and function [ 65 , 170 , 198 , 199 ].…”
Section: Lncrnas In Neurodevelopmental and Neuropsychiatric Disordersmentioning
confidence: 99%
“…It is quite common to observe coexisting diseases, such as epilepsy, depression or attention deficit hyperactivity disorder (ADHD) [ 109 ]. The development of ASD is caused by multiple factors, among which there are more than 130 genes [ 83 ]. It has been reported that some lncRNAs may also be involved in ASD pathogenesis, especially at the epigenetic level [ 117 ].…”
Section: Retro-lncrnas and Other Diseasesmentioning
confidence: 99%
“…Downregulation of MSN protein expression leads to inhibited activation of the PI3K/Akt signaling pathway. MNSP1AS is one of the major factors influencing the PI3K/Akt pathway, and the RhoA and Rac1 pathways are important for neuronal structure and survival [ 83 ]. It was reported that MSNP1AS and MSN are able to form dsRNA (double stranded RNA), which suppresses the expression of the protein encoded by the parental gene [ 83 , 118 , 119 ].…”
Section: Retro-lncrnas and Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the importance of lncRNAs in neuronal physiology it is not surprising that dysregulation of lncRNAs in the brain might be linked to neurodevelopmental disorders [ 160 , 161 ], autism spectrum disorders [ 162 , 163 , 164 ], substance use [ 165 ], intellectual disability [ 166 ], neurodegenerative diseases and neurological disorders [ 167 , 168 ]. A growing number of studies report that lncRNAs are associated with the pathology and development of neurodegenerative diseases [ 80 , 114 , 169 , 170 ].…”
Section: Lncrnas In Brain Disease and Neurodegeneration: Biomarkers Or Active Players?mentioning
confidence: 99%